2019
DOI: 10.1016/j.lwt.2018.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow thin film microfluidic mediated nano-encapsulation of fish oil

Abstract: A facile process has been developed for the encapsulation of fish oil using a thin film vortex fluidic device (VFD) operating under continuous flow, allowing control over the size of the encapsulated particles which are spheroidal in shape with diameters ranging from 50 to nm. This microfluidic platform simplifies the processing procedure of water-in-oil-in-water (w/o/w) encapsulation, as now a time and cost saving one-step process devoid of any organic solvents, in contrast to the conventional homogenization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In comparison with particle sizes of samples produced by homogenization, the particle sizes of samples produced by VFD are drastically reduced. The difference between encapsulated particle size using VFD and homogenization processing for different lipid surfactants was similar to that for low concentrations of lipid 14 . Furthermore, VFD processing is able to provide continuous processing, whereas homogenization is only able to provide batch processing.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…In comparison with particle sizes of samples produced by homogenization, the particle sizes of samples produced by VFD are drastically reduced. The difference between encapsulated particle size using VFD and homogenization processing for different lipid surfactants was similar to that for low concentrations of lipid 14 . Furthermore, VFD processing is able to provide continuous processing, whereas homogenization is only able to provide batch processing.…”
Section: Resultssupporting
confidence: 52%
“…The VFD was operated at optimized conditions, where the rotation speed was 9000 rpm, flow rate 0.3 mL/min, tilt angle 45°, and 25°C. The tilt angle of 45°has been reported as the optimal angle in many previous studies regarding VFD operation 9,10,14,16,17 . Our previous study 14 regarding fish oil encapsulation at low concentration also reported that the particle size of encapsulated fish oil was the smallest when the tilt angle was set at 45°while operating the VFD, as measured by dynamic light scattering (DLS).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations